1980
DOI: 10.1111/j.1600-0447.1980.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality in unipolar and bipolar manic‐melancholic patients

Abstract: By use of standardized case-recording criteria (MULTI-CLAD) manic-melancholic patients were classified as unipolar (n = 13) and bipolar (n = 23). Personality patterns are evaluated when patients were in neutral mood (defined by low symptom rating scale scores). Results showed that the similarities in the personality patterns of unipolars and bipolars were much pronounced than the differences. In general, the score patterns of the various scales in both groups of patients were found to be within the normal scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Similarly, Bagby et al [25] found that recovered patients with unipolar depression who were in remission from an episode of unipolar depression had lower levels of extroversion by one standard deviation than existed in a normal population. These results are consistent with the findings of Bech et al [26] and Murray and Blackburn [27], who found that recovered patients with recurrent unipolar depression had lower levels of extroversion. Similarly, Maier et al [28] found lower levels of extroversion in euthymic relatives of patients with affective disorder than in relatives of normal control individuals.…”
Section: Introversion As An Underlying Trait In Depressionsupporting
confidence: 92%
“…Similarly, Bagby et al [25] found that recovered patients with unipolar depression who were in remission from an episode of unipolar depression had lower levels of extroversion by one standard deviation than existed in a normal population. These results are consistent with the findings of Bech et al [26] and Murray and Blackburn [27], who found that recovered patients with recurrent unipolar depression had lower levels of extroversion. Similarly, Maier et al [28] found lower levels of extroversion in euthymic relatives of patients with affective disorder than in relatives of normal control individuals.…”
Section: Introversion As An Underlying Trait In Depressionsupporting
confidence: 92%
“…The CMPS has been used in several Swedish and Scandinavian studies, for instance, in an investigation on patients with affective disorders (Bech, Shapiro, Sihm, Nielsen, Sorensen and Rafaelsen, 1980;Bech, Jorgensen, Jeppesen, Loldrup Poulsen and Vangaard, 1986;Strandman, 1978), fertile women (Jacobsson, Perris and Espvall, 1979, and in elderly persons (Nilsson and Persson, 1984;Persson, 1980). and practically; difficulties in managing solely.…”
Section: Methodsmentioning
confidence: 99%
“…Both of them believed that the clinical effect of lithium resulted from a complex interaction of a large number of homeostatically regulated processes rather than from one single regulative action on an 'inborn' neurotransmitter, as had been supposed by the Lange brothers and by Cade. In the end of September 2005, during a scientific meeting in Poland, Schou suggested to carry out a study on the effect of lithium in patients with a 'hidden' bipolar disorder. It has been known for a long time that unipolars (patients with recurrent depressive episodes) who respond to long-term lithium therapy have a rather normal personality profile, similar to that found in bipolar disorder (50). When he returned from Poland, he developed a serious pneumonia, but despite this he continued to work with the protocol at home.…”
mentioning
confidence: 95%